OS10.4.A The effects of SmartCare on neuro-oncology family caregivers' distress: a randomized controlled trial. (9th September 2021) - Boele, F W; Weimer, J M; Proudfoot, J; Marsland, A L; Armstrong, T S; Given, C W; Drappatz, J; Donovan, H S; Sherwood, P R
Abstract: BACKGROUND: Patients with primary malignant brain tumors have high symptom burden and commonly rely on family caregivers for practical and emotional support. This can lead to negative mental and physical consequences for caregivers. We investigated effectiveness of an 8-week nurse-led online needs-based support program (SmartCare © ) with and without online self-guided cognitive behavioral therapy (CBT) for depression compared to enhanced care as usual (ECAU) on depressive symptoms, caregiving-specific distress, anxiety, mastery, and burden. MATERIAL AND METHODS: Family caregivers with depressive symptoms were randomized to three groups: SmartCare © plus/minus self-guided CBT, or ECAU. Primary outcomes (depressive symptoms (CES-D); caregiving-specific distress (Caregiver Needs Screen)) and secondary outcomes (anxiety (POMS-A), caregiver mastery (Caregiver Mastery Scale), and caregiver burden (Caregiver Reactions Assessment)) were assessed online. Intention to treat analyses of covariance corrected for baseline scores were performed for outcomes at four months. RESULTS: In total, 120 family caregivers participated. Accrual and CBT engagement were lower than expected, therefore intervention groups were combined (n=80) and compared to ECAU (n=40). For depressive symptoms, no statistically significant group differences were found. Caregiving-specific distress decreased in the intervention group compared with ECAU ( p =0.01, partial ɳ 2 =0.08). Among secondary outcomes, there was a trend towards improvement in mastery for the intervention group compared with ECAU ( p =0.08, partial ɳ 2 =0.04). CONCLUSION: SmartCare ©, with or without self-guided CBT, reduced caregiving-specific distress with a trend towards improving mastery. SmartCare © has the potential to improve the lives of families coping with a brain tumor diagnosis.